The Dynamic of Gender Role Conflict on Husbands of Pastors at Batak Karo Protestant Church - Karina Meriem Beru Brahmana (Journal of Educational, Health and Community Psychology, 2018)
Gender commonly correlates with condition of gender inequality experienced by women. However, we are unaware that men also experience gender inequality in their daily life that subsequently arises conflict within themselves known as gender role conflict. This study aimed to give description on conflict dynamics of gender role on husbands of pastors at the Batak Karo Protestant Church. Limited study on gender role conflict in men and negative effects resulted from this conflict encouraged the researcher to conduct this research. There were 3 participants involved, namely TA, SE, and BS. These three participants fulfilled the sample criteria: 1) Having been married for at least one year; 2) Having at least one daughter or son; 3) A native of Karo tribe; and 4) Having been a congregation at Batak Karo Protestant Church since childhood. The researcher used qualitative method with phenomenology approach, in which the interview results were analyzed using hermeneutic method. Hermeneutic method, or so-called interpretative phenomenology, is a method focusing on understanding the meaning of one's experience (by searching for themes), by involving a larger interpretive of available data and moving away from core search. The results showed that gender role conflict experienced by pastors’ husbands were caused by several factors, including gender role socialization since childhood, the influence of patriarchal culture embraced by the Karo tribe, masculine ideology and gender role transition that caused husbands to practice roles inconsistent with their gender role demand as a man. The writer encouraged more qualitative studies regarding this topic.Keywords: gender role, conflict, male